THE PROCESS OF DIGITIZING OF OLD GLOBE - Ambrožová, K.; Havrlanta, J.; Talich, M.; Böhm, O. (International archives of the photogrammetry, remote sensing and spatial information sciences., 2016)
This paper describes the process of digitalization of old globes that brings with it the possibility to use globes in their digital form. Created digital models are available to the general public through modern technology in the Internet network. This gives an opportunity to study old globes located in various historical collections, and prevent damage of the originals. Another benefit of digitization is also a possibility of comparing different models both among themselves and with current map data by increasing the transparency of individual layers. Digitization is carried out using special device that allows digitizing globes with a diameter ranging from 5 cm to 120 cm. This device can be easily disassembled, and it is fully mobile therefore the globes can be digitized in the place of its storage. Image data of globe surface are acquired by digital camera firmly fastened to the device. Acquired image data are then georeferenced by using a method of complex adjustment. The last step of digitization is publication of the final models that is realized by two ways. The first option is in the form of 3D model through JavaScript library Cesium or Google Earth plug-in in the Web browser. The second option is as a georeferenced map using Tile Map Service.